Multidisciplinary approach for a severe head burn caused by high-voltage electrical shock - a case report - Hoffman, Zofia; Homa, Piotr; Gałązka, Jakub Krzysztof; Sakwa, Leon; Szymoniuk, Michał; Domagalski, Łukasz; Wdowiak, Marcin; Czyżewski, Wojciech; Rola, Radosław; Antonov, Sergey (Journal of Education, Health and Sport, 2022)
In modern reconstructive medicine, personalized bone substitutes provide therapeutic hope for patients with non-standard bone defects. The study aims to present a description of a case of using a personalized bone substitute material, taking into account the vascular connections formed after a previous skin transplant. The 29-year-old patient was admitted to the plastic surgery department urgently after being electrocuted with high voltage. Due to extensive scalp burns, a skin graft was performed in the area of previously removed skin along with a charred skull bone vault. After a few months, the patient was qualified for cranioplasty with the use of personalized bone substitutes. The necessity to make cuts around the vascular connections present in the transplanted tissue was the main difficulty in the for the operator. The operation was successful and the recovery was uneventful. The patient was discharged home in good general and local condition. The presented case illustrates the need to take into account creating vascular connections with the use of personalized bone substitutes in patients after skin transplants.